2008
DOI: 10.1159/000151625
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Radiotherapy of Retrobulbar Orbit Metastases due to Breast Cancer

Abstract: Background: In breast cancer, the occurrence of retrobulbar metastases of the orbit is rare compared to intraocular metastases. The clinical symptoms are quite different. Impairment of vision, exophthalmus, double vision, vertigo, and pain reduce patients’ quality of life. Patients and Methods: The benefit of palliative irradiation of the orbit was researched retrospectively in 7 patients. This report also presents the first case in the literature of a breast cancer patient with bi-orbital enophthalmus caused … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Palliative treatment can reduce the nidus, relieve pain, and extend life so as to improve the life quality of patients. For example, previous research showed that palliative radiotherapy of retrobulbar metastases of breast cancer could reduce acute clinical symptoms [24]. In addition, palliative radiotherapy also played an important role in treating breast cancer with brain metastases and leptomeningeal carcinomatosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Palliative treatment can reduce the nidus, relieve pain, and extend life so as to improve the life quality of patients. For example, previous research showed that palliative radiotherapy of retrobulbar metastases of breast cancer could reduce acute clinical symptoms [24]. In addition, palliative radiotherapy also played an important role in treating breast cancer with brain metastases and leptomeningeal carcinomatosis [25].…”
Section: Discussionmentioning
confidence: 99%
“…En la mayor parte de las series publicadas se ha objetivado que la radioterapia produce regresión de la afectación tumoral orbitaria y/o de sus síntomas en el cáncer de mama. En una serie australiana se encontró este resultado en tres de las cinco pacientes que fueron irradiadas paliativamente 65 . Las metástasis orbitarias de cáncer de mama en localización retrobulbar tienen una buena respuesta sintomática a la radioterapia, con mejoría de los síntomas de dolor, exoftamos, enoftalmos, vértigo, diplopia y oftalmoplegia 66 .…”
Section: Tratamientounclassified